Prevalence and predictors of problematic smart phone use among pre-varsity young people in Ibadan, Nigeria (2020)
Introduction: smart phone possession and use among young people is on the increase in Africa and phone addiction has been shown to be similar to substance use dependence. However, there is barely any literature focused on the effect of smart phone use on young people in Nigeria. This study looked at the prevalence of problematic smart phone use and associated factors among prevarsity young people in Ibadan. Methods: problematic smart phone use was assessed using the 27-item mobile phone problem use scale and scored on a 5-point Likert scale. Scores 27-76 indicated low-moderate degree and scores ≥ 77 indicated moderate-severe degree of problematic smart phone use. Chi square test was used to compare problematic phone use with some selected respondents' characteristics and p was 0.05. Results: five hundred and seventy five participants were recruited, age range 14-24 years and 46.0% were males. Almost all (96.7%) of the respondents had smart phone access and 46.5% had moderate severe problematic phone use. Young people who were males, had their parents paying for the data they use, had high extroversion, low conscientiousness and low intellect scores were likely to have problematic phone use. The identified predictors for problematic phone use were male gender (OR=1.77, 95% CI: 1.26-2.50), high extroversion (OR=1.68, 95% CI: 1.16-2.43) and low conscientiousness (OR=2.09, 95% CI: 1.41-3.09). Conclusion: there was a high rate of problematic phone use among these young people. Interventions to promote responsible smart phone use are required to counter this problem.